The moderating role of negative affect on pain in patients with rheumatoid arthritis who have undergone shoulder arthroplasty - Lazaridou Asimina; Schneller Tim; Brune Daniela; Edwards Robert; Scheibel Markus (Journal of Orthopaedic Surgery and Research)
Abstract Objective Patients with rheumatoid arthritis undergoing shoulder arthroplasty often experience significant pain and functional limitations. Improvements in physical outcomes are well-documented, but psychological factors like negative affect remains underexplored. This study aimed to examine whether changes in negative affect moderate the relationship between functional and pain in rheumatoid arthritis undergoing shoulder arthroplasty. Methods We analyzed 92 patients with rheumatoid arthritis undergoing shoulder arthroplasty. Baseline and 6-month postoperative outcomes were assessed, including pain, shoulder function (SPADI), and negative affect. Moderation analysis was conducted to examine whether changes in negative affect influenced the relationship between functional improvements and pain reduction. Results The majority of patients were female (80%) with a mean age of 65 ± 11.1 years. Postoperative assessments showed significant improvements in pain and function. Pain scores decreased from a mean of 5.6 (SD = 2.6) to 1.2 (SD = 1.7) (p <.001), while SPADI scores improved from 63.7 (SD = 18.7) to 24.7 (SD: 15.9), (p <.001). Negative affect showed a reduction from 1.4 (SD = 0.7) to 1.2 (SD: 0.4), (p =.067). Persistent pain was present in 16% of patients postoperatively. Moderation analysis revealed a significant interaction between improvements in function and changes in negative affect on pain (β = 0.16, p =.017), suggesting that patients with concurrent emotional improvement experienced enhanced pain relief. Conclusion Shoulder arthroplasty in patients with rheumatoid arthritis reduces pain and improves function. Notably, improvements in negative affect may amplify the benefit of functional recovery on pain outcomes. These findings highlight the importance of integrating psychological well-being into postoperative care for this population.